Who was Clara Barton? - Spinner, Stephanie (Who was-- ?, 2014)
Profiles the life and accomplishments of Clara Barton, a teacher who organized efforts to bring nursing care to wounded soldiers during the Civil War and who went on to become the founder of the American Red Cross.